Peran Human Relation dalam Menciptakan Lingkungan Kerja yang Harmonis dan Produktif - Olivia Putri Andini; Sefia Darmayanti; Indah Fitria Sari; April Laksana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This study highlights the importance of implementing human relations principles in creating a harmonious and productive work environment. Open communication, empathy, and constructive conflict management were found to be key factors in building positive work relationships between employees and managers. Employees who feel valued and listened to tend to be more engaged in their work, increasing motivation and morale, which ultimately impacts the performance of the team and the organization as a whole. In addition, effective conflict management can strengthen interpersonal relationships and create a work atmosphere that is more conducive to collaboration and innovation. This study also shows that poorly managed conflict can damage work relationships and reduce productivity. In such situations, a tense work environment can lower employee morale, increase turnover rates, and hinder the achievement of organizational goals. Therefore, organizations need to actively develop strategies that support clear and effective communication, as well as pay attention to employee emotional well-being. Building an inclusive work culture and providing constructive conflict resolution mechanisms are essential to maintaining the stability and sustainability of productivity in the long term.